Internet communication issues: cross-cultural aspect - G N Trofimova (RUDN Journal of Language Studies, Semiotics and Semantics, 2012)
The article treats the issues of language functioning in the Internet communication, the peculiarities of speech strategies realizations, the linguistic conflictology.